Single molecule insights into mRNA dynamics in neurons - Buxbaum, Adina R. (Trends Cell Biol, 2015)
Targeting of mRNAs to neuronal dendrites and axons plays an integral role in intracellular signaling, development and synaptic plasticity. Single molecule imaging of mRNAs in neurons and brain tissue has led to enhanced understanding of mRNA dynamics. Here we discuss aspects of mRNA regulation as revealed by single molecule detection, which has led to quantitative analyses of mRNA diversity, localization, transport, and translation. These exciting new discoveries propel our understanding of the life of an mRNA in neurons and how its activity is regulated at the single molecule level.